1984
DOI: 10.1161/01.hyp.6.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chronic psychosocial hypertension in mice by decaffeinated tea.

Abstract: SUMMARY The effects of decaffeinated green tea on CBA mice have been contrasted with those of water during 3 to 5 months of exposure to various intensities of social stress. Intensity was modified by using different types of caging: Henry-Stephens complex population cages for maximum stress, open field population cages for intermediate levels, and siblings in standard mouse boxes for minimal stress. Two population densities were used: high, with 16 males and 16 females per population cage; and low, with approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 22 publications
0
49
0
2
Order By: Relevance
“…Caffeine, a major component found in green tea, is known for its psychoactive effects at low doses 24,34 -36 . A laboratory study reported that the administration of decaffeinated green tea in the drinking water of mice exposed to psychosocial stress resulted in significantly reduced physiological stress markers and behavioural responses 37 . Our results indicated an independent association between perceived mental stress and an increase in the risk of mental ill-health.…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine, a major component found in green tea, is known for its psychoactive effects at low doses 24,34 -36 . A laboratory study reported that the administration of decaffeinated green tea in the drinking water of mice exposed to psychosocial stress resulted in significantly reduced physiological stress markers and behavioural responses 37 . Our results indicated an independent association between perceived mental stress and an increase in the risk of mental ill-health.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, however, several authors reported hypotensive effects of tea after repeated dosage (Henry and Stephens-Larson 1984;Iwata et al 1987;Taniguchi et al 1988). For example, Iwata et al (1987) The major gap between the findings in animal experiments and the present observation is that the hypotensive effects of green tea was positive in animals whereas the apparent reduction in the proportion of those with the disease history is only in the case of stroke and not hypertension in the present epidemiological study.…”
Section: Discussionmentioning
confidence: 99%
“…While beneficial effects were investigated against cancer [1,2], vascular diseases [3], hypertension [4], and dental caries [5], tea was associated with dental [6] and skeletal [7] fluorosis, and Alzheimer's disease [8] due to accumulation of fluoride (F) and aluminum (Al), respectively, in the plant. The impact of tea drinks on human health has been observed, and trace elemental content of tea has been investigated in Southern Asian countries where tea is a traditional drink consumed in large quantities, such as in China [9], India [10], Taiwan [11], and Tibet [6] for fluoride, and in China [12], and Thailand [13] for aluminum and other trace elements.…”
Section: Introductionmentioning
confidence: 99%